2019
DOI: 10.1016/j.ejso.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Resection of GIST in the duodenum and proximal jejunum: A retrospective analysis of outcomes

Abstract: Introduction: Gastrointestinal stromal tumors (GISTs), with a primary occurrence in the duodenum and proximal jejunum, are rare and treatment is poorly understood. This study aimed to evaluate the main factors influencing the prognosis of GIST resection in this complex anatomical structure. Materials and methods: This retrospective study included 47 patients who underwent surgery for primary GIST of the duodenum (20) and proximal jejunum (27) between 2012 and 2017. Perioperative clinical data as well as relaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
1
10
0
2
Order By: Relevance
“…Las neoplasias duodenales primarias son raras y corresponden más frecuentemente a GIST. Por lo mismo, la evidencia se limita a series de casos que describen como único tratamiento curativo la resección 8 . Los adenocarcinomas de duodeno (excluyendo los ampulomas) son aún más raros, con un mal pronóstico debido a su diagnóstico tardío 5,9,10 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Las neoplasias duodenales primarias son raras y corresponden más frecuentemente a GIST. Por lo mismo, la evidencia se limita a series de casos que describen como único tratamiento curativo la resección 8 . Los adenocarcinomas de duodeno (excluyendo los ampulomas) son aún más raros, con un mal pronóstico debido a su diagnóstico tardío 5,9,10 .…”
Section: Discussionunclassified
“…El abordaje fue abierto en la mayoría de los casos, dado que se requería una resección en bloque (colon, riñón) o correspondían a casos de urgencia. La técnica laparoscópica fue una buena alternativa para el manejo de GIST limitados al duodeno 8 . Nuestra serie describe la experiencia con una técnica quirúrgica que, debido a lo infrecuente de su indicación, nos parece relevante dar a conocer.…”
Section: Discussionunclassified
“…While a stapled side-to-side anastomosis would have been the ideal and preferred approach to create the anastomosis, it was not possible in this case due to the short length of the proximal jejunal limb, which prevented the use of a stapler to connect the ends of small bowel. In other circumstances where the jejunojejunostomy cannot be safely created due to the proximity to the ligament of Treitz, other surgical options such as a gastrojejunostomy, duodenojejunostomy or more complex bowel reconstruction must be considered, although they may result in higher rates of complications and worse outcomes [ 12 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Our decision regarding the type of anastomosis to be created was based on the availability of only 5cm of proximal jejunum. Previous studies have shown no significant difference in anastomotic leak rates, morbidity or mortality between sutured versus stapled bowel anastomoses [ [12] , [13] , [14] ]. Today, while it is more common to perform a stapled anastomosis, the proximity of the proximal jejunal limb to the ligament of Treitz did not allow us to perform an adequately sized stapled side-to-side jejunojejunostomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that duodenal GIST are rare, the characteristics, prognosis, and optimal management have not been well clarified. More studies in the literature addressing the topic of duodenal GIST are limited by case reports [ 1 , 10 , 11 , 12 , 13 , 14 , 15 ] and small study populations [ 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. More rarely, there are larger single-/multi-institutional experiences [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%